Epidemiology and economic loss of coenurosis in small Ruminants slaughtered at mojo halal export abattoir, Oromia reginal state, East Shoa Zone, Ethiopia - Sagni Diba; Abebe Garoma (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Coenurosis is an important parasitic disease affecting small ruminant's production which causes significant economic losses. A cross-sectional study was carried out from November, 2019 to May, 2020. To estimating the prevalence of coenurosis in small ruminants and determines the risk factors, to assess the community knowledge on the epidemiology of coenurosis and estimate the financial loss due to brain condemnation. A total 674 small ruminants were by a simple random sampling procedure. Data was analyzed using STATA version 11. Chi square test and logistic regression analysis were used to determine the association between prevalence of coenurosis and potential risk factors. From the total 512 goat and 162 sheep examined for coenurosis 6.02% and 8.6% were found positive respectively. There was significance difference between the risk factors and coenurosis infection. More coenurosis infected small ruminants were found in highland 9.7% (Odd ratio= 2.31, 95% Confidence Interval: 1.14, 4.64; P=0.017) than midland and lowland. There was high prevalence of coenurois in adult than young age of small ruminants. From 45 positive cysts were examined to identify fertility and viability by using cyst viability and fertility procedure, 17.8% calcified, 68.9% sterile and 13.3 % fertile. The diameter of positive cysts showed 46.7%, 42.3%, 11% small, medium and large respectively. From 100 respondents' 86% of respondents has agreed on the sign of coenurosis, 14% has not agreed. The annual financial losses due to brain condemnation were estimated at 124,821 dollar.